Stability of dibromo-dipyrromethene complexes coordinated with B, Zn, and Cd in solutions of various acidities - Aksenova, Yulia V. (Molecules)
The spectral luminescent properties of dipyrromethenates halogenated with bromine on both ends of the long axis and coordinated using boron fluoride, zinc, or cadmium in neutral ethanol and acidified with hydrochloric acid solutions were studied. The constants of the acid–base equilibrium of the complexes in the proton-donor solvents in the ground and excited states was determined. The mechanisms of complex protonation were discussed, depending on the structure of the compounds. The electronic structures of the neutral and protonated compounds were modeled and analyzed based on the quantum-chemical method. The structures and spectral-luminescence properties were calculated using the SMD model of ethanol solvent using the TD-DFT theory with the B3LYP functional and the composite def2-SVP/def2-TZVP/def2-TZVPP_ECP basis sets, depending on the atomic number of the elements.